Intrinsic Elements and Moral Values in The Anthology of Aim Short Stories by Kholifatul Fauziah - Risma Tartila; Anggraini, Nori; Faizah, Punky Nurul (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
The selection of AIM's short story anthology aims to understand and know the aspects of structuralism and moral values. The research design used is descriptive qualitative. The source of the data for this study was the Anthology of the short stories Aim by Kholifatul Fauziah and DPND Class which were then chosen as the object of research because this anthology of short stories contains many elements of literary works and a clear moral message. This research was conducted in several stages, namely: (1) the planning stage, listening and reading carefully the AIM Short Anthology. (2) the implementation stage, collecting data, classifying and analyzing the structural approach in short stories. (3) the reporting stage, involving the writing and publication of the results of this research so that they can be read, known, and used by other people who need them. The results of the research show that the intrinsic structure in structural studies is in the form of themes, plot, characters and characterizations, setting, point of view, style of language, message, and moral values. This structure can be a successful builder of conveying the meaning of the story from the writer to the reader.